Tuina Massage Effectiveness on Weight Gain of Toddlers at BPM Cahaya Bunda Pekanbaru - Een Husanah; Miratu Megasari (Institute Of Computer Science (IOCS), 2021)
Toddler age is a vulnerable age, because growth at this time greatly determines subsequent physical and mental development. Good nutrition is an important element in creating a quality human being. Therefore, nutritious food intake is very important for the growth of brain cells and their physique (Annif Munjinah, 2015). Based on the author's experience in providing guidance to midwifery students who practice in the field, it is found that many parents carry out routine massage on their babies or toddlers with several the reasons for doing the massage include being fussy and not wanting to eat. This research aims to determine the effectiveness of tuina massage on weight gain for toddlers at BPM Cahaya Bunda Pekanbaru. This type of research is a quasi experimental (quasi-experimental) with a one group pretest posttest approach. Sampling in this study using accidental sampling technique. The population in this study were all toddlers who visited BPM to do massage. The analysis used was univariate and bivariate. The results showed that there was a significant difference between body weight before and after being given tuina massage therapy. Tuina massage is effective against weight gain in toddlers. The amount of benefits of Tuina Massage for toddlers is expected to be a complementary therapy in providing care for children who have eating problems so that the growth and development of toddlers can be optimal. The population in this study were all toddlers who visited BPM to do massage. The analysis used was univariate and bivariate. The results showed that there was a significant difference between body weight before and after being given tuina massage therapy. Tuina massage is effective against weight gain in toddlers. The amount of benefits of Tuina Massage for toddlers is expected to be a complementary therapy in providing care for children who have eating problems so that the growth and development of toddlers can be optimal. The population in this study were all toddlers who visited BPM to do massage. The analysis used was univariate and bivariate. The results showed that there was a significant difference between body weight before and after being given tuina massage therapy. Tuina massage is effective against weight gain in toddlers. The amount of benefits of Tuina Massage for toddlers is expected to be a complementary therapy in providing care for children who have eating problems so that the growth and development of toddlers can be optimal. Tuina massage is effective against weight gain in toddlers. The amount of benefits of Tuina Massage for toddlers is expected to be a complementary therapy in providing care for children who have eating problems so that the growth and development of toddlers can be optimal. Tuina massage is effective against weight gain in infants. The amount of benefits of Tuina Massage for toddlers is expected to be a complementary therapy in providing care for children who have eating problems so that the growth and development of toddlers can be optimal.